2022
DOI: 10.1002/jor.25364
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan in articular cartilage: Analysis of hip osteoarthritis and osteonecrosis of femoral head

Abstract: Hyaluronan (HA) plays crucial roles in the maintenance of high-quality cartilage extracellular matrix. Several studies have reported the HA in synovial fluid in patients with osteoarthritis (OA), but few have described the changes of HA in articular cartilage of OA or idiopathic osteonecrosis of the femoral head (ONFH). KIAA1199 was recently reported to have strong hyaluronidase activity. The aim of this study was to clarify the HA metabolism in OA and ONFH, particularly the involvement of KIAA1199. Immunohist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In this study, a total of 9 analytes were evaluated: matrix metalloproteinase (MMP)-1, MMP-2, MMP-3, MMP-10, and MMP-12 (EMD Millipore, catalog No HMMP2MAG-55K-04); tissue inhibitor of metalloproteinase (TIMP)-1 and TIMP-2 (EMD Millipore, catalog No HTMP1MAG-54K-02); aggrecan chondroitin sulphate neopepitope CS846 (IBEX, catalog No 60-1004); and hyaluronic acid (HA; R&D systems, catalog No DHYALO). Regarding these investigated items, it has been reported that MMPs and TIMPs are involved in cartilage degeneration, 13,30 HA in cartilage is reduced by OA, 32 and CS846 is a useful diagnostic marker for early OA that has received much attention in recent years. 2,14…”
Section: Methodsmentioning
confidence: 99%
“…In this study, a total of 9 analytes were evaluated: matrix metalloproteinase (MMP)-1, MMP-2, MMP-3, MMP-10, and MMP-12 (EMD Millipore, catalog No HMMP2MAG-55K-04); tissue inhibitor of metalloproteinase (TIMP)-1 and TIMP-2 (EMD Millipore, catalog No HTMP1MAG-54K-02); aggrecan chondroitin sulphate neopepitope CS846 (IBEX, catalog No 60-1004); and hyaluronic acid (HA; R&D systems, catalog No DHYALO). Regarding these investigated items, it has been reported that MMPs and TIMPs are involved in cartilage degeneration, 13,30 HA in cartilage is reduced by OA, 32 and CS846 is a useful diagnostic marker for early OA that has received much attention in recent years. 2,14…”
Section: Methodsmentioning
confidence: 99%
“…This decline in HA levels can be attributed to an imbalance between HA synthesis and degradation, with increased activity of hyaluronidases, the enzymes responsible for HA breakdown [ 71 ]. Consequently, the cartilage becomes vulnerable to wear and tear, resulting in pain, stiffness, and functional impairment [ 72 ]. Dysregulated HA metabolism, including increased synthesis and degradation, contributes to cartilage degradation, synovitis, and pain in OA [ 73 ].…”
Section: Pathophysiological Role Of Hyaluronic Acid In Rheumatic Dise...mentioning
confidence: 99%